Eksplorasi Linguistik Komputasional dalam Analisis Bahasa Alami untuk Mengungkap Evolusi Dialek Digital di Era Media Sosial Global - Ari Putra WIbowo; Nurul Hidayat (Journal of New Trends in Sciences, 2023)
The development of digital technology and social media has driven a major transformation in the study of linguistics, particularly in understanding the evolution of global languages and the emergence of digital dialects. Interactions on platforms such as Twitter, Instagram, and TikTok accelerate the formation of new vocabulary, the use of slang, and the spread of cross-cultural expression. Antony and Tramboo (2023) highlight the digital metamorphosis in language, while Friedrich and De Figueiredo (2016) explain the birth of digital Englishes in a sociolinguistic perspective. Language research challenges on social media have also emerged, such as the limitations of dialect processing (Jørgensen et al., 2015) and the influence of digital linguistic ecology (Klushina, 2022). Advances in natural language processing (NLP) have also strengthened this study. Cambria and White (2014) and Skaria et al. (2024) show the development of NLP from sentiment analysis to its application in education (Khensous et al., 2023) and multilingual text analysis (Agüero-Torales et al., 2021). The systematic review of Sundaram et al. (2023) and Prihatini et al. (2023) reinforces the evidence that social media expands language skills and enriches contemporary discourse, while Sun et al. (2021) show an increasing trend of digital linguistic research through bibliometric analysis, including cultural gaps (Rani & Samjetsabam, 2024). Overall, language not only evolves naturally, but also through human interaction with technology and digital culture. Digital dialects, slang, and online communication patterns are part of the global linguistic evolution that opens up interdisciplinary research opportunities between linguistics, computing, and cultural studies.